Suppliers Developing Customer Knowledge for Dataenabled Service Innovations - Saarnilinna, Marika; Momeni, Beheshte; Martinsuo, Miia (Finland, 2025)
Multiple companies may be involved in the development and delivery of data-enabled industrial services, so the flow of knowledge between companies is necessary and, yet, potentially problematic. The purpose of this paper is to increase understanding of customer knowledge development for data-enabled service innovations in the context of industrial services. We investigate manufacturer’s and technology supplier’s approaches to customer knowledge development on service innovations using a qualitative comparative case study. Our findings reveal six categories of drivers and barriers to developing customer knowledge: development priorities, customer service experience, customer knowledge diffusion, customer knowledge creation issues, organizational issues and inter-organizational issues. Two different approaches are identified for customer knowledge development, relationship-led approach and value-led approach, depending on the actor’s position in the supply chain. As managerial contribution our study suggests manufacturers to utilize technology supplier’s complementary approach for customer knowledge development to improve their service innovation processes.
Proceedings of The XXXV ISPIM Innovation Conference